Strategi Penghidupan Berkelanjutan Masyarakat Berbasis Aset di Sub DAS Pusur, DAS Bengawan Solo - Rathna Wijayanti; M. Baiquni; Rika Harini (Jurnal Wilayah dan Lingkungan, 2016)
In coping with water insufficiency and socio-economic culture problems, the strategy by combining the livelihoods assets which they have already owned and which are accessible has applied by the farmers at Pusur Sub-Watershed. The study aims to review the conditions of livelihoods assets owned and those which were accessible by the community, as well as to review the strategies of sustainable livelihoods of community-based on the asset in order to increase the living and to protect the environment sustainability in Pusur Sub-Watershed, Bengawan Solo Watershed. The method used was using quantitative and qualitative analysis through the questionnaire, in-depth interview, and observation techniques. The variables are used to value the condition of livelihoods assets are the human capital, natural capital, social capital, physical capital, and financial capital. The livelihood strategies were grouped into an intensification and extensification, diversification, and migration. The method of sampling area and purposive sampling are applied to split the area of research into three, i.e. the upper part, middle part, and bottom part. The result showed that the highest asset owned by Sub-Watershed on the middle part, upper and the last is a bottom part. The physical capital would have the highest value in the whole area of Sub-Watershed if it compared to the other capitals. The intensification strategy on the upper part is agroforestry, while the middle and bottom have “panca usaha tani” strategy. The diversification strategy through livestock is taken in the upper part, while the strategies as the employee or hourly workers are found in the middle and bottom part. The migration strategies with the reason of marriage were dominating in the bottom and upper parts, while the middle part the migration is due to the work issues.